Overshooting Indonesian Rupiah's Exchange Rate towards US Dollar: Dornbusch Model Hypotheses Test - Suidarma, I Made; Sanica, I Gede; Ayu, Putu Cita; Darma Diatmika, I Gusti Nengah (International Journal of Economics and Financial Issues, 2018)
The study aims at identifying the determinants of overshooting Indonesian Rupiah's exchange rate towards US Dollar and testing Dornbusch model hypothesis. The data applied are Indonesia monthly time series data in the period of 2010.1 – 2017.12. The Data source is Financial Economy Statistics of Indonesia from the Central Bank of Indonesia. The analysis method used is dynamic Vector Error Correction Model (VECM). Several variables employed are exchange rate, inflation level, economy growth, interest rate policy, money supplies and international interest rate. The result shows that in long term, money supply variable or monetary aggregate has negative relation to exchange rate movement in which the increase of money supply or monetary aggregate causes exchange rate depreciation. Short term shock does not affect exchange rate significantly. Dornbusch hypothesis on overshooting of exchange rate did not occur in Indonesia during the observation period. Keywords: Dornbush Overshooting, Exchange Rate, Fundamental Macroeconomic, VECM JEL Classifications: E10; F31; F41; C32